Neuroleptic Malignant Syndrome in an Octogenarian: A Case Report - Chapnick, Cary N. (1989)
Neuroleptic malignant syndrome is a potentially fatal and frequently undiagnosed consequence of the use of neuroleptics. We present a case report of the syndrome in an octogenarian, the second such to appear in the literature. This syndrome is reviewed and its importance in diagnosis and treatment of the elderly is indicated.